Large-scale RNA-Seq mining reveals ciclopirox olamine induces TDP-43 cryptic exons - Irika R. Sinha; Parker S. Sandal; Holly Spence; Grace D. Burns; Aswathy Peethambaran Mallika; Fatemeh Abbasinejad; Katherine E. Irwin; Anna Lourdes F. Cruz; Vania Wang; Shaelyn R. Marx; Josué Llamas Rodríguez; Ben Langmead; et al. (Nature Communications)
Abstract Nuclear clearance and cytoplasmic aggregation of TDP-43, initially identified in ALS-FTD, are hallmark pathological features observed across a spectrum of neurodegenerative diseases. We previously found that TDP-43 loss-of-function leads to transcriptome-wide inclusion of deleterious cryptic exons, a signature detected in presymptomatic biofluids and postmortem ALS-FTD brain tissue, but the upstream mechanisms that lead to TDP-43 dysregulation remain unclear. Here, we developed a web-based resource (SnapMine) to determine the levels of TDP-43 cryptic exon inclusion across hundreds of thousands of publicly available RNA sequencing datasets. We established cryptic exon inclusion levels across a variety of human cells and tissues to provide ground truth references for future studies on TDP-43 dysregulation. We then explored studies that were entirely unrelated to TDP-43 or neurodegeneration and found that ciclopirox olamine (CPX), an FDA-approved antifungal, can trigger the inclusion of TDP-43-associated cryptic exons in a variety of mouse and human primary cells. CPX induction of cryptic exons arises from heavy metal toxicity and oxidative stress, suggesting that similar vulnerabilities could play a role in neurodegeneration. Our work demonstrates how diverse datasets can be linked through common biological features and underscores how public archives of sequencing data remain a vastly underutilized resource with tremendous potential for uncovering novel insights into complex biological mechanisms and diseases.